Investigating the Impact of STEM Problem-Based Learning Intervention on Indonesian Pre-service Teachers’ Beliefs and Skills - Fitriani, Ella (Curtin University, 2025)
Traditional teaching methods in Indonesia remain entrenched, with a strong emphasis on content knowledge, often at the expense of fostering students’ skills. This study examined the impact of a STEM-Problem-Based Learning (PBL) intervention on Indonesian pre-service teachers' beliefs and skills. The intervention, aligned with the United Nations Sustainable Development Goals, led to a shift towards constructivist teaching approaches and improved collaboration, critical thinking, and digital literacies. The findings